Residential environmental livability in Nigeria: an overview - Bashari, Sunusi; Hashim, Ahmad Hariza; Abu Samah, Asnarulkhadi; Ahmad, Nobaya (Fakulti Sains Sosial dan Kemanusiaan, Universiti Kebangsaan Malaysia, 2018)
The purpose of this paper is to examine the problems of public low-cost housing in Nigeria and suggest some guiding principles that can be used for successful public low-cost housing for low-income people in Nigeria. This research was conducted through in-depth reviews of previous literatures and document related to public low-cost housing in Nigeria. National housing policy is among the document analysed by the researcher. The major constraints to public low-cost housing in Nigeria are that, the housing units are not liveable, because most of the residents are not satisfied with it. The housing units are characterized by indecent housing units, the needs and aspirations of the residents are neglected, safety and security challenges, poor location and difficult to access functional facilities. The main limitation of this research is no field survey or interview to collect data from the residents of public low-cost housing has been conducted. This research will assist housing policy makers and housing developers to understand the important of opinion or views of beneficiaries before and after construction of public low-cost housing. This will be achieve if certain attributes of housing are incorporated in the National Housing Policy as may be suggested by the beneficiaries. Recent studies in Nigeria have shown that, the quality level of building and infrastructural elements depend on cultural background of the beneficiaries. Presently, scholars in Nigeria are shifting towards housing design that will reflect the desire and expectations of beneficiaries through incorporating of culture of the people in housing design. This issue is of great significant to ASEAN region which comprises different cultural diversities, these differences in culture need to be considered in housing design not adopting standard from developed world. The findings of this paper were based on reviewed of earlier studies on residential environmental liveability particularly the public low-cost housing in Nigeria and the analysis of document of National Housing Policy. The findings of this study revealed some guiding principles that can help in solving public low-cost housing problems in Nigeria.